2019
DOI: 10.1530/rep-19-0285
|View full text |Cite
|
Sign up to set email alerts
|

miR-21-3p inhibits autophagy of bovine granulosa cells by targeting VEGFA via PI3K/AKT signaling

Abstract: It is well documented that granulosa cell apoptosis is the main reason for follicular atresia and death; however, increasing evidence suggests that autophagy plays an important role in the fate of granulosa cells. miR-21-3p regulates many fundamental biological processes and is pivotal in the autophagy of tumor cells; nevertheless, the autophagy in cattle ovary and how miR-21-3p regulates the follicular cells is unknown. In this study, we aimed to elucidate the autophagy and the role of miR-21-3p in cattle ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…Here, we demonstrated that autophagy and apoptosis occur in GCs in different stages of follicles and autophagy mainly occurs in GCs of medium follicles, while apoptosis mainly occurs in GCs of large follicles. However, autophagy was found in bovine granulosa cells of large follicles, while apoptosis was found in medium follicles [19]. These results showed variation between species.…”
Section: Discussionmentioning
confidence: 81%
“…Here, we demonstrated that autophagy and apoptosis occur in GCs in different stages of follicles and autophagy mainly occurs in GCs of medium follicles, while apoptosis mainly occurs in GCs of large follicles. However, autophagy was found in bovine granulosa cells of large follicles, while apoptosis was found in medium follicles [19]. These results showed variation between species.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, overexpression or knockdown studies using lentiviral transduction in bovine cumulus cells have shown that miRNAs such as miR-375 could affect oocyte maturation by targeting ADAM metallopeptidase with thrombospondin type 1 motif 1 (ADAMTS1) and progesterone receptor (PGR) genes [51]. Moreover, inhibitory role of miR-21-3p in utophagy, which determines the fate of granulosa cells, in bovine granulosa cells by targeting VEGFA via PI3K/AKT signaling has been documented [52]. Apart from these, in vitro functional studies have demonstrated that several miRNAs including miR-146a, miR-183-96-182 cluster, miR-383 and others are believed to regulate folliculogenesis or oocyte maturation by maintaining the survival and proliferation of granulosa/cumulus cells functions (Table 1).…”
Section: Functional Analysis Of Mirnas In Oocyte Companion Somatic Cellsmentioning
confidence: 98%
“…Moreover, autophagy of granulosa cells is suppressed by activation of the mTOR signalling pathway mediated by AKT during follicular atresia [15]. In our lab, thea previous study indicateds that BGC autophagy is involved in follicular atresia [3,4]. Although studies have elucidated the function of GC autophagy in follicular atresia and ovarian primordial follicular reserves [16], the regulatoryion mechanism of autophagy in GC is indistinct.…”
Section: Disscussionmentioning
confidence: 83%